Does the presence of blind-ended vas deferens and spermatic vessels in laparoscopic exploration of non-palpable testes conclusively indicate testicular absence? - Mao, Chang-Kun; Deng, Qi-Fei; Liu, Xiang; Cao, Yong-Sheng; Li, Guang-Yuan (Frontiers in Pediatrics, 2024)
The purpose of this study was to determine whether the presence of blind-ended vas deferens and spermatic vessels (VDSV) during laparoscopic exploration of non-palpable testes (NPT) indicates testicular absence or atrophy.A retrospective analysis was conducted on clinical data of patients diagnosed with NPT and treated with surgical intervention at our center from April 2013 to April 2023. The dataset encompassed information such as the children's age, affected side, size of the contralateral testis, surgical procedures employed, outcomes, and histopathological examination results. All patients underwent physical examination and ultrasonography preoperatively, followed by a combination of laparoscopic exploration and exploration through inguinal or scrotal incisions during surgery. Long-term follow-up was conducted postoperatively.Results: A total of 476 cases comprising 504 NPT were included in this study: 302 cases on the left side, 146 cases on the right side, and 28 cases bilaterally. All patients underwent surgical treatment within 6 to 126 months (median 13 months). During laparoscopic exploration, blind-ended VDSV were found in 90 testes (72 on the left side, 18 on the right side), while exploration through inguinal or scrotal incisions revealed 52 (57.8%) testicular nodules with atrophy, which were excised, leaving 38 (42.2%) without any findings. Histopathological examination of atrophic nodules revealed fibrosis as the most common finding in 41 cases (78.8%), followed by involvement of the vas deferens in 33 cases (63.5%), calcification in 24 cases (46.2%), epididymis in 23 cases (44.2%), and hemosiderin deposition in 7 cases (13.6%).Fibrosis, calcification, hemosiderin deposition, involvement of the vas deferens, and epididymis were found in combination in 47 specimens (90.4%). Seminiferous tubules (SNT) were found in 3 specimens (5.7%), and germ cells (GC) were found in 1 specimen (1.9%).The presence of blind-ended VDSV during laparoscopic exploration of NPT does not necessarily indicate testicular absence or disappearance. It is possible that atrophic testicular nodules are located within the inguinal canal or scrotum. This understanding contributes to the management of non-palpable testes. Considering their unpredictable malignant potential, we recommend excision.